Contrasting effects of the El Niño 2015–16 event on coral reefs from the central pacific coast of Mexico. (2nd February 2021) - Nava, Héctor; López, Norma; Ramírez‐García, Pedro; Garibay‐Valladolid, Elizabeth
Abstract: Coral reefs are highly diverse and productive ecosystems, and certain oceanographic processes, such as El Niño, have resulted in severe coral bleaching and mortality of reef‐building corals and to the global decline of the area covered by coral reefs. Here, we report the response of corals and both green and red filamentous and coralline algae from the central Mexican Pacific coast to the 2015–16 El Niño event. Sea surface temperature (SST) was recorded in the area between june 2012 and December 2018. Additionally, SST, DHW and the Oceanic El Niño Index (ONI) provided by NOAA for the El Niño 3 region during the same period were considered. Relative cover (%) of healthy, pale, bleached and dead corals, coral rubble, filamentous algae, rocks, and sand were recorded at five reefs during 2010, 2015, and 2018. Between April 2015 and April 2016, the SST was warmer than average, and the ONI showed temperature anomalies near 3, indicating a strong El Niño event. The response of corals varied among reefs and years. No relevant changes in substrata cover were recorded at two reefs through the years, but extensive coral bleaching occurred at the other reefs in June 2015, with dramatic coral mortality as a consequence. An inability to recover and the resulting dominance of filamentous algae over dead corals was evident at two reefs in January 2018. Multivariate analysis based on the cover of substrata and the comparison with previous studies suggested that the response of the coral reefs was not related to the previous state of conservation or the level of anthropogenic impact at each reef. The causes of such thermal resistance are uncertain; nonetheless, it has a high potential to cope with future El Niño impacts.